Análise comparativa da fotobiomodulação com uso de laser e LED em indivíduos portadores de disfunção temporomandibular: projeto piloto - Langella, Luciana Gonçalves (2019)
Temporomandibular dysfunction (TMD) is described as a subgroup of Orofacial pain. Studies have shown that phototherapy has been an efficient alternative in the treatment of DTMS by improving pain and orofacial function. Objective: To compare the effects of photobiomodulation on pain and functionality in patients with TMD. Methods: This was a controlled, double-blind, randomized clinical trial (pilot study) involving 15 individuals aged over 18 years old distributed in 2 groups: Laser and LED being followed up by 8 sessions 2 times a week, totaling 4 weeks of Treatment. The diagnostic criterion for TMD research (RDC) was used to evaluate all study participants, then pain was evaluated through the use of Visual analogue scale and orofacial function through the measurements of the maximum mouth opening. Photobiomodulation was applied to the Temporomandibular joint (TMJ), masseter muscles (upper, middle and lower) and anterior temporal. Results: When comparing the data regarding the variable pain, statistically significant differences were found only in the intra-group analysis pre and post treatment with photobiomodulation (laser p = 0,0117 and LED p = 0,0180); There was no statistically significant difference in pre-and post-treatment analyses between and within laser and LED groups for maximum aperture measurements without help and without pain. For maximum opening without aid and maximum opening with aid there were statistically significant differences for the laser Group (p = 0.0203; p = 0.0001, respectively); The same was observed for the LED only at the maximum opening with aid (P = 0,0459). For the right and left lateral excursion measurements, a statistically significant difference was found before and after treatment for the laser group in both lateralities (right side p = 0,0209; left side p = 0,0005) and only left for the LED Group (p = 0.0342). Conclusion: Photobiomodulation with laser and LED can produce similar effects for pain and improve the orofacial function. The LED therapy can possibly be pointed as an interesting alternative in the treatment of patients with temporomandibular dysfunction.